Analisis Metode Bermain Peran (Role Playing) Untuk Meningkatkan Keterampilan Berbicara Pada Mata Pelajaran Bahasa Indonesia - Siti Hardiyanti; Budiana; Ahmad Hidayat (Jurnal PGMI UNIGA, 2025)
This study aims to analyze the implementation of the role-playing method in improving students’ activeness and learning quality at Islamic elementary school. This research employed a qualitative descriptive approach. The subjects of the study were fifth-grade students totaling 22 students and the classroom teacher, while the object of the study was the application of the role-playing method in the learning process. Data were collected through observation, interviews, and documentation. The results of the study indicate that the role-playing method is effective in increasing students’ activeness in learning. Students become more enthusiastic, confident to perform in front of the class, actively participate in discussions, and understand the learning material more easily. The role-playing method also creates an enjoyable learning atmosphere, increases learning motivation, and develops students’ communication and collaboration skills. Moreover, experience-based learning through role-playing helps students relate the learning material to real-life situations, making learning more meaningful. Therefore, the role-playing method can be used as an effective alternative learning method to improve the quality of learning in Islamic elementary schools. Keywords: Role Play Method, Learning Activity, Language Indonesia